Surface-enhanced Raman scattering of self-assembled thiol monolayers and supported lipid membranes on thin anodic porous alumina - Salerno, Marco; Shayganpour, Amirreza; Salis, Barbara; Dante, Silvia (Beilstein Journal of Nanotechnology, 2017)
Thin anodic porous alumina (tAPA) was fabricated from a 500 nm thick aluminum (Al) layer coated on silicon wafers, through single-step anodization performed in a Teflon electrochemical cell in 0.4 M aqueous phosphoric acid at 110 V. Post-fabrication etching in the same acid allowed obtaining tAPA surfaces with ≈160 nm pore diameter and ≈80 nm corresponding wall thickness to be prepared. The tAPA surfaces were made SERS-active by coating with a thin (≈25 nm) gold (Au) layer. The as obtained tAPA–Au substrates were incubated first with different thiols, namely mercaptobenzoic acid (MbA) and aminothiol (AT), and then with phospholipid vesicles of different composition to form a supported lipid bilayer (SLB). At each step, the SERS substrate functionality was assessed, demonstrating acceptable enhancement (≥100×). The chemisorption of thiols during the first step and the formation of SLB from the vesicles during the second step, were independently monitored by using a quartz crystal microbalance with dissipation monitoring (QCM-D) technique. The SLB membranes represent a simplified model system of the living cells membranes, which makes the successful observation of SERS on these films promising in view of the use of tAPA–Au substrates as a platform for the development of surface-enhanced Raman spectroscopy (SERS) biosensors on living cells. In the future, these tAPA–Au-SLB substrates will be investigated also for drug delivery of bioactive agents from the APA pores.
Keywords: anodic porous alumina; SERS; nanopores; supported lipid bilayers; thiols

(untitled) - Diggle, J. W.; Downie, T. C.; Goulding, C. W. (Chem. Rev., 1969)

Nanostructured Materials in Electrochemistry - Sulka, G. D. (Wiley-VCH, 2008)

(untitled) - Karlsson, M.; Johansson, A.; Tang, L.; Boman, M. (Microsc. Res. Tech., 2004)

(untitled) - Salerno, M.; Caneva-Soumetz, F.; Pastorino, L.; Patra, N.; Diaspro, A.; Ruggiero, C. (IEEE Trans. NanoBioscience, 2013)

(untitled) - Gentile, F.; Tirinato, L.; Battista, E.; Causa, F.; Liberale, C.; di Fabrizio, E. M.; Decuzzi, P. (Biomaterials, 2010)

(untitled) - Ross, A. M.; Jiang, Z.; Bastmeyer, M.; Lahann, J. (Small, 2012)

(untitled) - Rahmany, M. B.; Van Dyke, M. (Acta Biomater., 2013)

(untitled) - Yanagishita, T.; Masuda, H. (AIP Adv., 2016)

(untitled) - Yanagishita, T.; Masuda, H. (Electrochim. Acta, 2015)

(untitled) - Santos, A.; Kumeria, T.; Losic, D. (TrAC, Trends Anal. Chem., 2013)

(untitled) - Chung, A. J.; Huh, Y. S.; Erickson, D. (Nanoscale, 2011)

(untitled) - Toccafondi, C.; Thorat, S.; La Rocca, R.; Scarpellini, A.; Salerno, M.; Dante, S.; Das, G. (J. Mater. Sci.: Mater. Med., 2014)

(untitled) - Toccafondi, C.; La Rocca, R.; Scarpellini, A.; Salerno, M.; Das, G.; Dante, S. (Appl. Surf. Sci., 2015)

(untitled) - Kneipp, K.; Kneipp, H.; Kneipp, J. (Acc. Chem. Res., 2006)

(untitled) - Nie, S.; Emory, S. E. (Science, 1997)

(untitled) - Gultepe, E.; Nagesha, D.; Sridhar, S.; Amiji, M. (Adv. Drug Delivery Rev., 2010)

Nanoporous Alumina: Fabrication, Structure, Properties and Applications - Aw, M. S.; Bariana, M.; Losic, D. (Nanoporous Anodic Alumina for Drug Delivery and Biomedical Applications, 2015)

(untitled) - Toccafondi, C.; Zaccaria, R. P.; Dante, S.; Salerno, M. (Materials, 2016)

(untitled) - Swan, E. E. L.; Popat, K. C.; Desai, T. A. (Biomaterials, 2005)

(untitled) - Chang, P.-C.; Liu, B.-Y.; Liu, C.-M.; Chou, H.-H.; Ho, M.-H.; Liu, H.-C.; Wang, D.-M.; Hou, L.-T. (J. Biomed. Mater. Res., Part A, 2007)

(untitled) - Tamm, L. K.; McConnell, H. M. (Biophys. J., 1985)

(untitled) - Das, G.; Patra, N.; Gopalakrishnan, A.; Zaccaria, R. P.; Toma, A.; Thorat, S.; Di Fabrizio, E.; Diaspro, A.; Salerno, M. (Analyst, 2012)

(untitled) - Thorat, S.; Diaspro, A.; Scarpellini, A.; Povia, M.; Salerno, M. (Materials, 2013)

(untitled) - Das, G.; Patra, N.; Gopalakrishanan, A.; Proietti Zaccaria, R.; Toma, A.; Thorat, S.; Di Fabrizio, E.; Diaspro, A.; Salerno, M. (Microelectron. Eng., 2012)

(untitled) - Zheng, J.; Zhou, Y.; Li, X.; Ji, Y.; Lu, T.; Gu, R. (Langmuir, 2003)

Course Notes on the Interpretation of Infrared and Raman Spectra - Mayo, D. W.; Miller, F. A.; Hannah, R. W. (Wiley, 2004)

(untitled) - Velleman, L.; Bruneel, J.-L.; Guillaume, F.; Losic, D.; Shapter, J. G. (Phys. Chem. Chem. Phys., 2011)

(untitled) - An, H. H.; Han, W. B.; Kim, Y.; Kim, H.-S.; Oh, Y.; Yoon, C. S. (J. Raman Spectrosc., 2014)

(untitled) - Taylor, R. W.; Benz, F.; Sigle, D. O.; Bowman, R. W.; Bao, P.; Roth, J. S.; Heath, G. R.; Evans, S. D.; Baumberg, J. J. (Sci. Rep., 2014)

(untitled) - Schulz, H.; Baranska, M. (Vib. Spectrosc., 2007)

(untitled) - Köhler, M.; MacHill, S.; Salzer, R.; Krafft, C. (Anal. Bioanal. Chem., 2009)

(untitled) - Zumbusch, A.; Langbein, W.; Borri, P. (Prog. Lipid Res., 2013)

(untitled) - Czamara, K.; Majzner, K.; Pacia, M. Z.; Kochan, K.; Kaczor, A.; Baranska, M. (J. Raman Spectrosc., 2015)

(untitled) - Richter, R. P.; Bérat, R.; Brisson, A. R. (Langmuir, 2006)

(untitled) - Reimhult, E.; Höök, F.; Kasemo, B. (Langmuir, 2003)

(untitled) - Peng, P.-Y.; Chiang, P.-C.; Chao, L. (Langmuir, 2015)

(untitled) - Campiña, J. M.; Martins, A.; Silva, F. (J. Phys. Chem. C, 2007)

Analysis of metal ions in water using SAM-modified EQCM electrodes - Hewas, A. M. (Department of Chemistry, University of Leicester, 2013)